Highlights of the IFPRI and FAO partnership: Working together to ensure food and nutrition security - International Food Policy Research Institute (International Food Policy Research Institute, 2016)
For four decades, the rich partnership between the Food and Agriculture Organization of the United Nations (FAO) and the International Food Policy Research Institute (IFPRI) has generated cutting-edge technical knowledge and enhanced expertise in support of food security and improved nutrition for all, and for making agriculture and food systems more inclusive, productive, resilient, and sustainable. Driven by these shared goals, FAO and IFPRI have contributed to a strong evidence base to strengthen the capacity of policy makers in making sound policy decisions. Our work helped create important information resources and networks for food security, strengthen the focus on gender in agriculture, spur strategic public investment in agriculture, promote productive and sustainable rural development, and advocate for enhancing the positive impact of agriculture and food systems on nutrition. This brochure presents highlights and successes of the partnership between FAO and IFPRI.